2008
DOI: 10.1007/s00436-007-0862-7
|View full text |Cite
|
Sign up to set email alerts
|

Cystic echinococcosis in equids in Italy

Abstract: Between March 2003 and February 2007, the livers and the lungs of 2,231 horses from various Italian regions were examined for cystic echinococcosis presence at the time of slaughter. Hydatid cysts were found in six horses, namely four from Sardinia, one from Sicily, and one from Tuscany. The location, number, morphology, and fertility of the cysts found were determined. DNA was extracted from the germinal layers and protoscoleces of the fertile cysts and polymerase chain reactions (PCR) were performed in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 19 publications
1
31
2
3
Order By: Relevance
“…Echinococcus equinus (G4) has been documented in horses from Spain and Italy Varcasia et al, 2008a) and E. ortleppi (G5) was found in cattle from Italy and France Grenouillet et al, 2014). In a study conducted in France by Grenouillet et al, 2014), evidence of liver infections caused by E. ortleppi was reported in two humans.…”
Section: U N C O R R E C T E D P R O O F S0360 3442 Molecular Epidmentioning
confidence: 99%
See 1 more Smart Citation
“…Echinococcus equinus (G4) has been documented in horses from Spain and Italy Varcasia et al, 2008a) and E. ortleppi (G5) was found in cattle from Italy and France Grenouillet et al, 2014). In a study conducted in France by Grenouillet et al, 2014), evidence of liver infections caused by E. ortleppi was reported in two humans.…”
Section: U N C O R R E C T E D P R O O F S0360 3442 Molecular Epidmentioning
confidence: 99%
“…In 2008, the presence of G2 in water buffaloes from southern Italy (a Mediterranean area) was reported for the first time Casulli et al, 2008;, and (Calderini et al, 2012) reported the occurrence of the G3 genotype in goats. Echinococcus granulosus (G1eG3) has been (Maurelli et al, 2015) and in humans in the Campania region, E. intermedius (G7) in pigs in Sardinia , E. ortleppi in cattle in the Lombardy region , and E. equinus in horses of Tuscany, Sardinia and Sicily Varcasia et al, 2008a). p1110…”
Section: U N C O R R E C T E D P R O O F S0360 3442 Molecular Epidmentioning
confidence: 99%
“…The intermediate hosts of E. equinus are equids (horses, donkeys, and zebras) (Jenkins et al, 2005). Other Echinococcus species may also cause CE in horses, however those cysts are not usually fertile (Varcasia et al, 2008). Canids (dogs and probably foxes) serve as definitive hosts of E. equinus (Thompson and McManus, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a hydatid cyst isolated from the lungs of a mare was identified as E. equinus in southern Germany (Blutke et al, 2010). Varcasia et al (2008) identified both E. equinus and E. granulosus s.s. in horses, although cysts of the latter showed aberrant morphological characters and were never fertile. Utuk and Simsek (2013) also reported the E. granulosus s.s. in a horse hydatid cyst isolate in Turkey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation